Environment and Territory community project: management and disposal of solid waste in the rural district of Pueblo Viejo, Moniquirá, Colombia - Pita Morales, Luz Adriana; Páez Saavedra, Julián David; Puerta Gutiérrez, Nasly Susana (Cooperativismo & Desarrollo, 2016)
Purpose: This article aims to share the progress of community work in the field of solid waste management in the rural district of Pueblo Viejo in the town of Moniquirá, Boyacá, Colombia. Topics: The increasing environmental damage caused by improper disposal of solid waste results in the degradation of resources and landscapes in rural areas. It is therefore necessary to provide accompaniment and interact with the residents of the district in a way that responds to the need for community and inter-institutional action in the face of environmental problems caused by waste. Development: The project was developed with a mixed approach in which the constructivist descriptive method was used to guide the exercise. Conclusions: The results reflect the way in which the residents of the district of Pueblo Viejo perceive their territory and the impact of solid waste on that territory, as well as the impact of entities that in one way or another have had an influence with regard to this topic in the region. An awareness campaign on the care of natural resources in the region was carried out, beginning at rural schools with the residents of the district.